Legal Perspectives on the Risks of Medical Malpractice in the Implementation of Artificial Intelligence and Telemedicine Technologies - Jubaidi, Didi; Khoirunnisa, Khoirunnisa (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2025)
The rapid development of Artificial Intelligence (AI) and telemedicine has transformed healthcare delivery by improving efficiency, accessibility, and patient reach. Nevertheless, these innovations raise significant legal challenges, particularly regarding medical malpractice, diagnostic accuracy, doctor–patient communication, and the protection of sensitive medical data. This study aims to examine the potential risks of medical malpractice arising from the use of AI and telemedicine and to evaluate their broader legal implications for patient safety and healthcare quality. The research employs a literature review and case law analysis, focusing on health regulations governing the integration of AI and telemedicine in medical practice. Using a descriptive and comparative approach, this study explores dimensions of legal responsibility, including the liability of healthcare providers, technology developers, and medical professionals. The findings indicate that errors in AI-based medical diagnosis may generate liability due to algorithmic failures, while telemedicine creates legal concerns in communication that affect clinical accuracy. In addition, patient data protection remains a critical issue due to risks of data breaches. The study concludes that comprehensive regulations are urgently needed to ensure data security, establish mechanisms for monitoring AI algorithms, and provide adequate training and certification for medical professionals in utilizing these technologies.